A Carbon Fixation Enhanced Chlamydomonas reinhardtii Strain for Achieving the Double-Win Between Growth and Biofuel Production Under Non-stressed Conditions - Zhu, Zhen; Cao, Huijiao; Li, Xu; Rong, Junfeng; Cao, Xupeng; Tian, Jing (Frontiers in Bioengineering and Biotechnology, 2021)
The stressed cultivations are widely used in microalgae R&D for the biofuel production with the repress on growth to a certain degree, which limits the overall productivity. The balance between the growth and energy storage compounds accumulation is a target needing the combination of both strain selection or construction and culture optimization. Here, an engineered strain of Chlamydomonas reinhardtii, in which the chloroplast type glyceraldehyde-3-phosphate dehydrogenase (cGAPDH) was overexpressed and named as P3-GAPDH, was cultured on the Algal Station platform. Compared with wild type (WT), C. reinhardtii CC137c, in Tris-acetate-phosphate (TAP) medium, the highest density of WT and P3-GAPDH were 1.23±0.13 g L-1 and 1.74±0.09 g L-1 within 96 hours, and the maximum biomass productivity was 24.30±1.65 mg L-1 h-1 and 28.54±1.43 mg L-1 h-1, respectively. In terms of the energy storage compounds, both carbohydrate and fatty acids content doubled in P3-GAPDH, from 0.13±0.02 g L-1 to 0.26±0.04 g L-1 for carbohydrate and from 0.08±0.01 g L-1 to 0.16±0.01 g L-1 for fatty acids, among which poly unsaturated fatty acids increased by 65.8%. Together with the continuous monitor of the chlorophyll fluorescence dynamics parameters Fv/Fm and Fv’/Fm’ and pH of culture, enhanced Calvin cycle by overexpressed cGAPDH promoted the carbon conversion and subsequent energy storage compounds accumulation. C. reinhardtii P3-GAPDH strain showed the potential as a good chassis with high carbon conversion ability.